Unmanned Aerial Vehicles in the Security Service and as a New Tool in the Hands of Criminals - Krakowiak Ewelina (Safety & Defense, 2018)
The aim of the article is to show areas in which unmanned aerial vehicles are used for protection purposes and to show that drones are increasingly used for criminal purposes, an important aspect is also to present the possibilities offered by these devices. Increasingly, new technologies are used daily in human activities. They become supportive, and at the same time, they facilitate many activities. With the introduction of unmanned aerial vehicles, they have become an object that has been adopted in many industries, from simple flight operations, to filming and shooting, to complex transport or search. Due to the many constraints inherent in the human factor, the necessity of introducing drones into many everyday industries has been recognized. Particular attention has been paid to unmanned aerial vehicles in the area of security and protection, where daily activities involve a high risk of human loss. For this purpose, new technologies are introduced, but drones, due to their characteristics and many other factors, a tool used by criminals for the purposes of trade, data theft, illegal shooting and photographing. These are just a few of the offences committed by means of unmanned aerial vehicles. This poses a threat and conducive to the emergence illegal market using drones.